CLASSROOM INTERACTION: A KEY TO FACILITATE LEARNING - Ratmanida Ratmanida (Universitas Negeri Padang, 2015)
The study aims to investigate factors that facilitate learning based on classroom interaction analysis at Fledgling Intemational Standard Schools known as Rintisan Sekolah Bertaraf Internasional (RSBI). The purposes of this study are in particular to find out how the interactions that take place between teacher student, student-teacher, and student-student facilitate learning. The site ofthe research is the Public Senior High Schools located in Padang that are implementirrg RSBI programmes; and the participants are Physics teachers along with their students. Data of this study is drawn from direct classroom observation, questionnaire and intensive intervierw and these data'were analyzed quantitatively and qualitatively. Data analyses reveal the following results. Some ofthe lactors that facilitates learning appeared to be constructive explanation, teacher's response to the students' question. and sharing ideas between or among students the so-called collaborative learning.